Child Development and Nutritional Status in Ecuador. (January 2019) - Huiracocha-Tutiven, Lourdes; Orellana-Paucar, Adriana; Abril-Ulloa, Victoria; Huiracocha-Tutiven, Mirian; Palacios-Santana, Gicela; Blume, Stuart
We assessed the development, nutritional status, and complementary feeding of 12- to 23-month-old children from Cuenca, Ecuador in 2013. Ecuador, an upper-middle-income country, developed a child policy in accordance with World Health Organization (WHO) guidelines. We collected cross-sectional survey data. Child development was assessed using the Integrated Management of Childhood Illness Guide–2011. The nutritional status was defined with WHO Child Growth Standards−2006. We investigated nutrient density, WHO Infant and Young Child Feeding Indicators, and nutrient supplementation intake of the complementary feeding. In all, 11.7% of children had "possible developmental delay, " stunting was identified in 29.4% of the children, and 25.3% faced overnutrition (overweight risk/overweight/obesity). The complementary feeding composition can be summarized as having adequate fat, high energy (MJ/day) and protein, and low iron and zinc. Children with "possible developmental delay" received less iron ( P < .05) than children with normal development. Overall, 30.4% of children had minimum dietary diversity. A total of 47.7% of children received nutrient supplementation. This epidemiological profile of infants remains a challenge for Ecuador's health programs.